2014
DOI: 10.1039/c4tc01349b
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis and electrical transition in p-type delafossite CuAlO2

Abstract: Highly polycrystalline and pure delafossite phase CuAlO 2 powder has been synthesised within a short annealing period, shorter than most conventional processes. This is an improvement over the conventional synthesis procedures. Conventional synthesis procedure has seen CuAlO 2 only formed at high annealing temperatures ≥ 1100°C over long annealing time, some as long as 96 hours. In the current process, a pure phase devoid of impurities has been obtained at reduced calcination time of 1.5 hours in an argon atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
4
8
0
2
Order By: Relevance
“…In addition, CuAlO 2 exhibits anisotropic behaviour in terms of electrical conductivity and the random orientation of the grains has a negative effect on the conductivity [1,52]. The electrical conductivity of the sample produced at 1150 °C in this study is comparable with the previously reported results in the literature using air atmosphere sintering at temperatures above 1100 °C [18,27,38] …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, CuAlO 2 exhibits anisotropic behaviour in terms of electrical conductivity and the random orientation of the grains has a negative effect on the conductivity [1,52]. The electrical conductivity of the sample produced at 1150 °C in this study is comparable with the previously reported results in the literature using air atmosphere sintering at temperatures above 1100 °C [18,27,38] …”
Section: Resultssupporting
confidence: 86%
“…The difficulty in achieving reduced temperature formation stems from the thermodynamic instability of CuAlO 2 below 1000 °C in air, yielding CuO and CuAl 2 O 4 phases involving Cu 2+ cation [37]. In a recent study, it was shown that the reaction times could significantly be reduced by flowing argon during firing [38]. CuAlO 2 was obtained via solid state reaction in 1.5 h via isothermal firing at 1150 °C and inert atmosphere quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Problems occurring with CuO x melts in Pt crucibles were already reported by several authors, e.g. [25,26] and are related to the formation of solid solutions between Pt and Cu. Both metals crystallize in f cc structure and the binary phase diagram Cu-Pt is in the high T range > 1000 • C almost ideal.…”
Section: Resultsmentioning
confidence: 79%
“…The copper‐based delafossite oxide semiconductors CuMO 2 (M = Cr, Ga, Al) have become much attractive in recent years due to their room‐temperature p‐type conductivity and wide direct bandgap . These characteristics are favorable for constructing p–n junction and have promising applications in optoelectronics .…”
Section: Introductionmentioning
confidence: 99%
“…The copper-based delafossite oxide semiconductors CuMO 2 (M ¼ Cr, Ga, Al) have become much attractive in recent years due to their room-temperature p-type conductivity and wide direct bandgap. [1][2][3][4][5][6] These characteristics are favorable for constructing p-n junction and have promising applications in optoelectronics. [7] The intrinsic p-type conductivity in CuMO 2 is attributed to the ionized interstitial oxygen atoms and ionized Cu vacancies.…”
Section: Introductionmentioning
confidence: 99%